1986
DOI: 10.1007/bf00297114
|View full text |Cite
|
Sign up to set email alerts
|

The toxicity and teratogenicity of mercuric mercury in the pregnant rat

Abstract: Mercuric mercury (Hg2+), when injected IV into the pregnant Wistar rat, is retained mainly in the maternal compartment and uptake by the conceptuses is small. Thus if the dose is based on total body weight, the maternal body burden, particularly in late gestation, is greater than the whole body burden in the non-pregnant animal. The LD50 of Hg2+ (mg/kg total body weight), however, remains essentially constant (1.0-1.2 mg Hg2+/kg) throughout pregnancy. It seems, therefore, that the rat becomes more resistant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 19 publications
2
5
1
1
Order By: Relevance
“…This i s in agreement with other studies that indicated a high tendency toward permeability of the placenta to methylmercury (Pitkin et al, 1975;Suzuki et al, 1971;Koos & Longo, 1976 Kuhnert et al (1981) found the highest concentration of inorganic mercury was in the placenta, suggesting a barrier role, but a significant correlation (r = .62) was also found between the maternal and fetal plasma inorganic mercury levels. Animal data are also in agreement with human observations (Gale & Ferm, 1971;Gale & Hanlon, 1976;Gale, 1981;Holt & Webb, 1986). It has been recently reported that exposure of human placental cells to mercury caused the accumulation of metal in the membranes and lowered the membrane fluidity (Boadi et al, 1992).…”
Section: Discussionsupporting
confidence: 86%
“…This i s in agreement with other studies that indicated a high tendency toward permeability of the placenta to methylmercury (Pitkin et al, 1975;Suzuki et al, 1971;Koos & Longo, 1976 Kuhnert et al (1981) found the highest concentration of inorganic mercury was in the placenta, suggesting a barrier role, but a significant correlation (r = .62) was also found between the maternal and fetal plasma inorganic mercury levels. Animal data are also in agreement with human observations (Gale & Ferm, 1971;Gale & Hanlon, 1976;Gale, 1981;Holt & Webb, 1986). It has been recently reported that exposure of human placental cells to mercury caused the accumulation of metal in the membranes and lowered the membrane fluidity (Boadi et al, 1992).…”
Section: Discussionsupporting
confidence: 86%
“…This i s in agreement with other studies that indicated a high tendency toward permeability of the placenta to methylmercury (Pitkin et al, 1975;Suzuki et al, 1971;Koos & Longo, 1976 Kuhnert et al (1981) found the highest concentration of inorganic mercury was in the placenta, suggesting a barrier role, but a significant correlation (r = .62) was also found between the maternal and fetal plasma inorganic mercury levels. Animal data are also in agreement with human observations (Gale & Ferm, 1971;Gale & Hanlon, 1976;Gale, 1981;Holt & Webb, 1986). It has been recently reported that exposure of human placental cells to mercury caused the accumulation of metal in the membranes and lowered the Downloaded by [Chulalongkorn University] at 03:16 27 December 2014 membrane fluidity (Boadi et al, 1992).…”
Section: Discussionsupporting
confidence: 89%
“…In Japan, 2,252 peoples have been affected and 1,043 have died due to Minamata disease, caused by elevated mercury pollution from a chemical plant (Kudo and Miyahara 1991). Even at very low concentration, Hg can cause permanent damage to the human central nervous system because LD 50 (rat) of Hg is 1-1.2 mg Hg 2+ /kg (Holtt and Webb 1986). Maximum contamination level or permissible limit for Hg is 0.001 mg L −1 (Bureau of Indian Standards 1983).…”
Section: Introductionmentioning
confidence: 98%